Trends and factors associated with intimate partner sexual violence among married women in Zambia: A multilevel analysis - Simona Simona; Nakena Likando (PLoS ONE, 2025)
Background Sexual violence against women is a major social and public health problem with wide-ranging consequences on the victims. In Zambia, 15% of women have experienced sexual violence from intimate partners. While there exist some studies on sexual violence in Zambia, there is a dearth of research specifically addressing underlying determinants of intimate partner sexual violence against women who are either married or living with partners. Our study sought out to examine factors associated with sexual violence among this demographic and how these factors vary across communities and over time. Method We used data from the 2007, 2013/14 and 2018 waves of the Zambia Demographic and Health Surveys (ZDHS) consisting of a total of 21,020 women of reproductive age group of 15-49 years old. Trends in intimate partner sexual violence by selected factors across the three ZDHS cycles were analyzed using bivariate statistics and multilevel logistic regression models. Multilevel models were also fitted on the pooled data, including all the survey years, to examine individual and contextual level factors associated with intimate partner sexual violence. Results The results show that the prevalence of sexual violence remain high in Zambia, with a slight decrease over time, from 16.3% in 2007 through to 14.7% in 2018. Trends analysis show that the prevalence rate among women who have attained higher education, are in the highest wealth quintile, reside in urban areas, have decision-making authority have decreased significantly between 2007 and 2018. Contrarily, among women who tolerate violence and those who live with alcohol consuming partners, sexual violence prevalence rates have increased over time. In the consolidated multilevel model, the study finds several factors to be associated with intimate partner sexual violence, including having primary education (AOR =  1.18; 95% CI 1.02-1.36), having an alcohol consuming partner (AOR =  1.76; 95% CI 1.61-1.93), having no decision-making authority (AOR =  1.19; 95% CI 1.09-1.31), witnessing parental violence (AOR =  1.47; 95% CI 1.34-1.60), having a controlling partner (AOR =  3.41; CI 2.96-3.92) and being in a polygynous relationship (AOR =  1.31; 95% CI 1.16-1.49). While women who occupy the highest wealth quintile (AOR =  0.72; 95% CI 0.57-0.90) and those who live in rural areas (AOR =  0.83; 95% CI 0.72-0.96) have lower odds of experiencing intimate partner sexual violence. Conclusion This study underscores the persistent prevalence of sexual violence against women in Zambia, particularly within the context of intimate relationships. While there has been a slight decrease in prevalence over time, there are significant disparities across demographic and socio-economic factors. Findings indicate that educational attainment, partner’s controlling behavior, decision making authority, exposure to parental violence, partner’s alcohol consumption, and relationship type significantly influence the likelihood of experiencing intimate partner sexual violence in Zambia. These findings imply that there is need for targeted policy interventions and strategies to address underlying determinants of intimate partner sexual violence and promoting gender equality and empowerment among women in Zambia.